Phosphodiesterase 10A as a Therapeutic Target in Neuropsychopharmacology: A Review - A. R. Dorotenko; I. M. Sukhanov; G. V. Iskarevskii; A. S. Ulitina; A. A. Savchenko; M. А. Tur (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Phosphodiesterases (PDEs) are enzymes that regulate intracellular signalling by catalysing the hydrolysis of cyclic nucleotides. The commercial success of selective PDE5 inhibitors for erectile dysfunction and PDE4 inhibitors for respiratory and skin diseases has drawn the close attention of pharmaceutical companies to other PDEs as well. PDE10A, which is expressed in medium spiny neurons (MSNs) of the striatum, deserves special attention as a promising target in psychopharmacology.AIM. This study aimed to analyse existing preclinical and clinical data on the use of PDE10A inhibitors and to assess possible barriers to the development of medicinal products of this class in neuropsychopharmacology.DISCUSSION. Preclinical studies have shown that PDE10A inhibitors, which increase the levels of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) in MSNs, have antipsychotic and antiparkinsonian properties. Some researchers also believe that PDE10A inhibitors improve cognitive functions. Despite the promising results of preclinical studies, clinical trials of PDE10A inhibitors have not been successful. This review analyses the possible reasons for these failures, including a poor understanding of the function of striatal PDEs in both normal and pathological conditions, the possible development of tolerance to some effects of PDEs, the complex interactions of intracellular cAMP and cGMP signalling pathways, and the intricate workings of the cortico-striato-thalamo-cortical (CSTC) circuits.CONCLUSIONS. Further research is needed to fully assess the therapeutic potential of PDE10A inhibitors, with a more detailed investigation of the mechanism of action of PDEs, the activity of MSNs, and the CSTC circuits. New data at these three levels of study (subcellular, cellular, and systemic) will create conditions for further development of PDE10A inhibitors.